2008
DOI: 10.1017/s1751731108002942
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of water intake, dry matter intake and daily milk yield using different error covariance structures

Abstract: The aim of the present study was to investigate the daily measured traits milk yield, water intake and dry matter intake with fixed and random regression models added with different error covariance structures. It was analysed whether these models deliver better model fitting in contrast to conventional fixed and random regression models. Furthermore, possible autocorrelation between repeated measures was investigated. The effect of model choice on statistical inference was also tested. Data recording was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…The error covariance was modelled due to the fact that repeated daily measurements within the lactation of sow were assumed to contain autocorrelated repeated measures (Kramer et al, 2008b;Littell et al, 1998;Littell et al, 2006). The covariance of the residual term was modelled with the spatial (exponential) structure (SP(EXP)).…”
Section: Discussionmentioning
confidence: 99%
“…The error covariance was modelled due to the fact that repeated daily measurements within the lactation of sow were assumed to contain autocorrelated repeated measures (Kramer et al, 2008b;Littell et al, 1998;Littell et al, 2006). The covariance of the residual term was modelled with the spatial (exponential) structure (SP(EXP)).…”
Section: Discussionmentioning
confidence: 99%
“…These values correspond to the second stage "Dynamic" of the methodology. Water consumption for watering animals that was obtained in the FDS of the Amecameca Sub-Basin is higher (5.6 l of water per liter of milk) in comparison with what was reported by various authors (Kume et al, 2010;Kramer et al, 2008;Nosetti et al, 2002;Meyer et al, 2004) (Table 1), because most of the studies reported were carried out with factors and conditions that were totally different than those evaluated in this research; for example, geographic region, milk production systems, type of diet, irrigation to obtain fodder, period of lactation, physiological stage, climate, season of the year, among others. The value obtained in this study represents more than double what was reported by Kume et al (2010), with a value of 2.66 liters of water per liter of milk per bovine head of breeding stock.…”
Section: Water Consumption In the Family Dairy Systemmentioning
confidence: 46%
“…Estos valores corresponden a la segunda etapa "Dinámica" de la metodología. El consumo de agua para abrevar que se obtuvo en el SFL de la Subcuenca Amecameca es mayor (5.6 l de agua por L de leche) en comparación con lo reportado por diversos autores (Kume et al, 2010;Kramer et al, 2008;Nosetti et al, 2002y Meyer et al, 2004) (Cuadro 1), debido a que la or no more than five employees), and humid (they are the establishments that require a consumption of 76 to 150 m 3 bimonthly to perform their activities). According to the Gazette of the Estado de México Government (2012), ranches and establishments were classified within the humid use.…”
Section: Consumo De Agua Dentro Del Sistema Familiar Lácteounclassified
See 1 more Smart Citation
“…Therefore, the error covariance needed to be modeled. Acceptable residuals were performed with the first-order heterogeneous autoregressive structure (Littell et al, 2006;Kramer et al, 2008;Kruse et al, 2010).…”
Section: Discussionmentioning
confidence: 99%